Nigerian organized crime - Williams, Phil (Henry Stewart Talks, 2008)
The rise of Nigerian crime, Nigeria itself, Emergence of Nigerian criminal organizations, Framework for analysis, The activities of Nigerian criminals, National level: opportunities, incentives, pressures and resources, Global level: opportunities, incentives, pressures and resources, Portfolio of domestic criminal activities, Portfolio of transnational criminal activities, Drug trafficking, Trafficking of women, Nigerian financial fraud, Advance fee or 4-1-9 frauds, The structure of criminal organizations
Archived at 2022/04/03